The Flipside of the Power of Engineered T Cells: Observed and Potential Toxicities of Genetically Modified T Cells as Therapy - Bedoya, Felipe (Mol Ther, 2017)
Autologous T cells modified to recognize novel antigen targets are a novel form of therapy for cancer. We review the various potential forms of observed and hypothetical toxicities associated with genetically modified T cells. Despite the focus on toxicities in this review, re-directed T cells represent a powerful and highly effective form of anti-cancer therapy; we remain optimistic that the common toxicities will become routinely manageable and that some theoretical toxicity will be exceedingly rare, if ever observed.